1997
DOI: 10.1046/j.1360-0443.1997.92910875.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethical, scientific and clinical issues in ethanol administration research involving alcoholics as human subjects

Abstract: Research involving the administration of ethanol to human subjects has been conducted with some regularity since the 1960s. The purpose of this paper is to provide a broader discussion of the ethical and clinical issues pertaining to the administration of ethanol to subjects with a history of alcohol dependence and to assess the potential benefits and risks of ethanol administration research. Three kinds of investigation are reviewed: (1) basic scientific research on alcohol dependence and related disabilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 11 publications
2
29
0
Order By: Relevance
“…Findings from human laboratory studies involving the direct administration of alcohol have advanced our knowledge of alcoholism etiology 1,2 and treatment development. 3 Nonetheless, the field has been challenged to determine the balance between the risks and benefits posed by administering alcohol to alcohol-dependent participants.…”
Section: Background and Objectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from human laboratory studies involving the direct administration of alcohol have advanced our knowledge of alcoholism etiology 1,2 and treatment development. 3 Nonetheless, the field has been challenged to determine the balance between the risks and benefits posed by administering alcohol to alcohol-dependent participants.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…4,5 However, studies to date have found no evidence of adverse consequences to alcohol-dependent individuals who participate in alcohol administration studies. 2,4 A few studies have tested whether direct alcohol administration poses a risk for alcohol-dependent individuals. Drobes and Anton 6 investigated the drinking patterns of 25 alcohol-dependent participants in their study of the effects of naltrexone on response to alcohol cues and alcohol administration.…”
Section: Background and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In our heroin studies, there was no difference in outcome on naltrexone at follow-up in the community between subjects who had received naltrexone on the unit (blocking the effects of heroin) and those who experienced unblocked heroin during 10 days of access [7]. Subsequently, our studies in alcoholics given an alcohol challenge and followed-up in the community showed no effect on compliance with the medication disulfiram [8] or on treatment outcome [9], compared with subjects who had not participated in the research.…”
Section: A: Exciting Times?mentioning
confidence: 99%
“…According to Cohen, it is only ethical to give drugs of dependence in experimental studies to abstinent addicts and possibly those who are in treatment. Even though research suggests that alcohol-and drug-dependent people who participate in research are helped rather than harmed (e.g., Dolinsky & Babor, 1997;Gorelick et al, 1999), we anticipate that ethics committees will not approve studies that administer drugs of dependence to abstinent addicts. If ethics review committees accept Cohen's argument, the outcome could be that no experimental research will be undertaken in which drug-dependent people receive their drug of dependence.…”
Section: Are Drug-dependent People Vulnerable Persons?mentioning
confidence: 99%